Positive Affective and Enjoyment Responses to Four High-Intensity Interval Exercise Protocols. Issue 4 (August 2020) - Marques, Marcelo; Alves, Elaine; Henrique, Nayana; Franchini, Emerson
Several variables can be manipulated to compose high-intensity interval exercise (HIIE) protocols, and these different combinations may evoke different psychological responses (affect, enjoyment, mood, and perceived exertion). This study investigated psychological responses during four HIIE protocols. Following anthropometric measurements and two maximal exercise tests, 23 physically inactive adults (11 males [ M age  = 25.6, SD  =   4.8 years; M body mass  = 68.5, SD  =   12.2 kg; M height  = 1.72, SD  =   0.08 m] and 12 females [ M age  = 25.0, SD =  3.5 years; M body mass  = 57.2, SD  =   8.7 kg; M height  = 1.59, SD  = 0.06 m]) performed four different types of HIIE on different days: (a) Long-interval HIIE (HIIEL —10 × 60 seconds:60 seconds), (b) Short-interval HIIE (HIIES —2 blocks of 10 × 30 seconds:30 seconds with 120 seconds between blocks), (c) Repeated Sprint Training (19 × 6 seconds all out:40 seconds), and (d) Sprint Interval Training (4 × 30 seconds all-out efforts: 240 seconds). We used a final session to assess participants' HIIE preference. We recorded participant reports of affect, mood, and perceived exertion throughout protocols, and we recorded enjoyment after exercise session. Perceived exertion significantly increased across all HIIE protocols ( p  <   .001), with higher values in the first quartile during Sprint Interval Training versus HIIEL ( p  =   .033). Affective response presented higher values pre-exercise and at the first quartile compared with all other moments ( p  <   .001). Tension ( p  <   .001) and depression ( p  =   .013) decreased from pre- to post-exercise in all experimental conditions. At pre-exercise, female participants were tenser than males ( p  =   .018), though males presented higher pre-exercise vigor scores than females ( p  =   .023). Vigor increased over time for females ( p  =   .022). Enjoyment did not vary between sexes or protocols. Participants expressed a higher preference for Repeated Sprint Training. HIIE protocols promoted positive psychological responses for physically inactive young adults, and exercise designs may modulate psychological responses.